STRUCTURAL CHANGES IN RATS’ OVARIES AFTER HORMONAL THERAPY FOR PRECANCEROUS CONDITIONS - Shamrai, D.V.; Melnyk, N.O. (World of Medicine and Biology, 2020)
Ovarian cancer is a principal cause of death and accounts for 25% among all gynecological tumors. The aim of this study is to establish efficacy of hormonal treatment for precancerous conditions in rats’ ovaries. We used modified Biskind’s method and made intramuscular injections of gonadotropin-releasing hormone agonist for precancerous conditions treatment. We described morphological changes in rats’ ovaries in different terms of hormonal treatment. Thus, from the 30th day, this leads to total hydropic degeneration of ovarian cells or atrophy of the ovary. From the 60th day the treatment is still effective, however we can observe collection of luteal cells with normal cytoplasm. From the 90th day, it is no longer effective and doesn’t lead to degeneration of cells, we observe follicular and lutein elements in the ovary with cellular atypism signs. Thus, from the 90th day, the ovarian tissue becomes resistant to hormonal influence and the treatment is ineffective.